Cross-sectional study on the relationship between physiologic and mental health status and hypertension risk among oil workers in Xinjiang - Song, Zhixin; Ma, Xiaofan; Li, Xue; Liu, Jiwen (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHypertension is a major global risk factor for cardiovascular disease. According to the 2023 Global Hypertension Report, its prevalence among adults aged 30–79 years is 33%, closely mirrored in China at 31.6% (2023 Cardiovascular Health and Diseases in China Report). The etiology of hypertension is multifactorial, involving psychological stress (impacting neuroendocrine and inflammatory pathways) and abnormal lipid metabolism. However, the association between mental health and biomarkers in occupational groups, particularly oil workers, remains unclear.PurposeThis study using a cross-sectional design to deeply analyze the associations between mental health, physiologic health and hypertension, and to explore the influencing factors of hypertension. It aims to provide a scientific basis for the prevention and treatment of hypertension among oil workers, and also to offer theoretical support for further formulating effective measures to improve the physical and mental health levels of oil workers.Materials and methodsA cluster sampling method was used to recruit 6,083 active oil workers from the Occupational Health Examination Department of Karamay Central Hospital in Xinjiang, China, from September 2018 to September 2019. Physiologic health status was randomly assessed in 20% of the participants to analyze the dose-response relationship between mental health, physiologic health, and hypertension. Based on the restricted cubic spline model, we explored the dose-response relationship between biochemical indicators and hypertension under different levels of mental health.ResultsThe results showed that the prevalence of hypertension among the study population was 18.4%, with significant differences observed across various demographic factors (gender, age, education, marital status, monthly income, work experience, job type, professional title, shift work, cigarette smoking, and alcohol consumption; P < 0.05). There was also a statistical difference in the prevalence of hypertension among different mental health states (P < 0.05), with a higher prevalence (25.5%) among those with poor mental health. Triglycerides [TG] (OR: 2.11; 95% CI: 1.82–2.45), lactate dehydrogenase [LDH] (OR: 1.02; 95% CI: 1.01–1.02) and low-density lipoprotein-cholesterol [LDL-C] (OR: 1.95; 95% CI: 1.65–2.30) emerged as risk factors for hypertension. After adjusting for confounding factors, TG, LDH, and LDL-C remained significant risk factors, with TG abnormalities conferring a 1.71-fold higher risk of hypertension (OR: 1.71; 95% CI: 1.43–2.05), LDH abnormalities conferring a 1.01-fold higher risk (OR: 1.01; 95% CI: 1.01–1.02), and LDL abnormalities conferring a 1.32-fold higher risk (OR: 1.32; 95% CI: 1.06–1.64). In the group with poor mental health, before adjusting for confounders, elevated levels of TG (OR: 3.08; 95% CI: 1.92–4.96), LDH (OR: 1.02; 95% CI: 1.01–1.03), and LDL-C (OR: 2.26; 95%CI: 1.46–3.51) all increased the risk of hypertension. After adjustment, TG (OR: 4.17; 95% CI: 1.86–9.31) and LDH (OR: 1.02; 95% CI: 1.01–1.04) remained significant risk factors. A linear dose-response relationship was noted between TG and LDH levels, and hypertension risk (TG: P for trend < 0.001, P for non-linearity = 0.056; LDH: P for trend = 0.008, P for non-linearity = 0.114).ConclusionIn conclusion, a dose-response relationship existed between mental health, TG and LDH levels, and hypertension risk. Attention should be paid to the mental health of oil workers and effective measures should be taken to alleviate mental health issues. Regular monitoring of blood lipid levels is crucial to reduce the risk of hypertension.